Prevalence of overweight and obesity in Mozambique in 2005 and 2015 - Fontes, F (2019)
Objective: The ongoing demographic, nutritional and epidemiological transitions in sub-Saharan Africa highlight the importance of monitoring overweight and obesity. We aimed to assess the prevalence of overweight and obesity in Mozambique in 2014/2015 and compare the estimates with those obtained in 2005. Design: Cross-sectional study conducted in 2014/2015, following the WHO Stepwise Approach to Chronic Disease Risk Factor Surveillance (STEPS). Prevalence estimates with 95 % CI were computed for different categories of BMI and abdominal obesity, along with age-, education- and income-adjusted OR. The age-standardized prevalence in the age group 25-64 years was compared with results from a STEPS survey conducted in 2005. Setting: Mozambique. Participants: Representative sample of the population aged 18-64 years (n 2595). Results: Between 2005 and 2014/2015, the prevalence of overweight and obesity increased from 18 center dot 3 to 30 center dot 5 % (P < 0 center dot 001) in women and from 11 center dot 7 to 18 center dot 2 % (P < 0 center dot 001) in men. Abdominal obesity increased among women (from 9 center dot 4 to 20 center dot 4 %, P < 0 center dot 001), but there was no significant difference among men (1 center dot 5 v. 2 center dot 1 %, P = 0 center dot 395). In 2014/2015, the prevalence of overweight and obesity was more than twofold higher in urban areas and in women; in the age group 18-24 years, it was highest in urban women and lowest in rural men. Conclusions: In Mozambique, there was a steep increase in the prevalence of overweight and obesity among adults between 2005 and 2014/2015. Overweight and obesity are more prevalent in urban areas and among women, already affecting one in five urban women aged 18-24 years.